Catheter-Directed Treatment for Pulmonary Embolism in Light of Current Evidence - Osman Ahmed; Alexandria Shadid (The Arab Journal of Interventional Radiology)
Pulmonary embolism (PE) is the leading cause of in-hospital morbidity and mortality and accounts for approximately 100,000 deaths in the United States and 300,000 deaths in Europe annually. Although societal guidelines for low- and high-risk PE are well established, the present management of submassive (intermediate)-risk PE is evolving. Catheter-directed thrombolysis (CDT) represents a viable treatment option for treatment of submassive PE given its ability to rapidly reduce right heart strain with an acceptably low rate of major hemorrhagic complication. The current review aims to discuss the existing guidelines and literature supporting CDT for PE and also to examine upcoming areas of future research to support its adoption in the algorithm for the management of submassive PE.